Analysing the physical condition and materials of the Kruger House wallpaper and proposing conservation treatment - Loubser, Maggi (University of Pretoria, 2024)
Mini Dissertation (MSocSci (Heritage and Cultural Sciences Heritage Conservation))--University of Pretoria, 2024.